KEMAMPUAN LITERASI SAINS SISWA PADA MATERI VIRUS PANDEMI COVID-19 DI SMAN 3 LUWUK - Moh. Fahri Haruna; Nurlia Nurlia; Suci Levianti (Bio-Lectura : Jurnal Pendidikan Biologi, 2023)
Students' scientific literacy in virus material is important to know their ability to read, write, or speak to get information or knowledge from various sources on virus material. the purpose of this study was to look at the scientific literacy skills of Luwuk 3 Public High School students during the Covid-19 pandemic. The data collection technique used in this study consisted of observation, filling out the instrument by students. This type of research questionnaire is in the form of multiple choice questions that are used to measure students' scientific literacy abilities, namely students' understanding in identifying scientific problems, explaining phenomena scientifically and using scientific evidence. data analysis using descriptive statistical analysis. Based on the results of the research and discussion, the researcher can conclude that of the 3 indicators measured, namely, the first identifies a scientific issue with a bad category present value (35.57%), the second explains the phenomenon scientifically with a moderate present value (50.75%) , and third, utilizing scientific evidence with a percentage value in the sufficient category (54.73%). The present results for all categories show that the scientific literacy skills of SMAN 3 Luwuk students regarding the Covid-19 virus are in the sufficient category with a percentage value of 47.39%.